Heat, moisture, and momentum budgets of a midlatitude squall line with a trailing stratiform region - Gallus, William A., author (Colorado State University. Libraries, 1989)
Rawinsonde data from the 1985 O-K PRE-STORM project are used to calculate the heat, moisture and momentum budgets during the late mature through decaying stages of a large squall line system that occurred on 10-11 June. Rawinsondes are composited to decrease station spacing and allow better resolution of mesoscale features within t he system. Low-level radar data and surface accumulated rainfall reports are used to partition the convective system into convective line and stratiform regions, and to check the accuracy of the heat and moisture budgets. Despite the compositing approach, the spacing of the sounding data is inadequate to fully resolve motions in the convective line. The resolution is marginally adequate, however, for motions in the stratiform region. This squall line had a pronounced rear-inflow jet that advanced toward the front of the system with time, and strong front-to-rear flow at higher levels. Convergence was strong in mid-levels within the stratiform region where the opposing jets met. Divergence at the top of the system weakened markedly as the system decayed. Upward vertical motion also weakened, and the vertical axes of strongest convective line ascent and descent within the stratiform region became increasingly sloped over time. Heating rates within the overall convective system peaked around 400 mb near the convective line region, and decreased in intensity from over 13°C h - 1 to less than 5°C h - 1 between 0300 and 0730 UTC. Cooling occurred in the stratiform region and was most intense just behind the back edge of the radar echo around 550 mb, just above the melting level. Peak cooling rates increased from over 3°C h- 1 to 6°C h- 1 between 0300 and 0600 UTC, and then decreased to 4°C h - 1 at 0730 UTC. Drying rates peaked also in the convective line region, but at lower levels than the heating rates. Moistening due to evaporation was typically strongest around 700 mb in the stratiform region. Vertical integrations of both budgets produced rainfall rates generally close to the observed ones for averages over the entire system. However, precipitation in the leading convective line was underestimated by 40% , due in large part to inadequate sounding data resolution. In the stratiform region the diagnosed precipitation rates underestimated the observed by as much as 2 or 3 _mm h-1 as the system decayed. Radar reflectivity data showed that the rearward transport · of hydrometeors could add as much as 2 - 4 mm h- 1 to the diagnosed stratiform rates. The transport, in addition to liquid water storage, could account for the underestimations in the diagnosed rates. The fact that the underestimate in the stratiform region did not occur at 0300 UTC suggests that vertical motion in the convective line was aliased into the stratiform region significantly at this earlier time. Less aliasing may have occurred later as the leading line weakened and the separation between it and the stratiform region increased. In general, the location of predicted rainfall and the temporal trend of the heating and moistening rates matched observations well, establishing the credibility of the budget studies. A strong mesolow existed at mid-levels within the stratiform region of the system, and the momentum budget showed pressure gradient accelerations were generally front-to-rear. Coriolis accelerations and internal turbulent stresses generally opposed the pressure gradient, and the resulting observed accelerations became weak, with increasing rear-to-front acceleration at high levels as the system weakened. The pressure gradient increased the vertical shear of the component of the wind normal to the line, but as the system decayed, the turbulent stresses began to oppose the increase in shear.
October 1989.
Also issued as author's thesis (M.S.) -- Colorado State University, 1989.
Keywords: Numerical weather forecasting; Meteorology -- Mathematical models